Close Encounters of the Victorian Kind The Sci-Fi Fundamentalism of Philip Henry Gosse - Grainger, Brett (2021)
It has been common to associate Victorian speculative literature—a broad literary genre characterized by supernatural, fantastical, or futuristic themes—with liberal religious movements, such as deism. Despite the cultural significance of evangelicalism during the Victorian era, evangelical works have been excluded from the genre. The late religious works of Philip Henry Gosse, especially his collection The Mysteries of God (1884), expand our understanding of speculative literature in late 19th-century British culture. At a time when the rapid pace of political, scientific, and technological developments spurred Jules Verne and H. G. Wells to imagine the future of human civilization, evangelicals such as Gosse turned an alternative speculative lens on the deep future. In essays such as "The Colonization of Worlds" and "The New Jerusalem," Gosse fused emergent narratives of secular progress and technological mastery with older eschatological traditions anticipating the millennial reign of Christ. While many late-Victorian evangelicals abandoned postmillennial hope for premillennial anxiety, Gosse exuded confidence in his ability to harmonize biblical literalism with speculative schemes of interplanetary colonization directed by Providence. This visionary spirit drew upon habits of spiritual eclecticism common to 19th-century evangelicalism, which combined biblical literalism, natural science, poetic imagination, and even esoteric traditions, such as pyramidology. Gosse's writings also illuminate broader cultural tensions of the period, between Romanticism and rationalism, observation and imagination, naturalism and supernaturalism, revelation and naturalism. For all of these reasons, his fantastic and idiosyncratic literary visions deserve to be remembered alongside other works of Victorian speculative literature.